Electric Cardiometry is not Predictive of Outcome in Full-term Newborns with Respiratory Distress: A Single Center Study - Esraa Ahmed Elmazzahy; Salma Zoheir Elhouchi; Eman Samir Khater; Khaled Amin Ahmed (Cairo University, Faculty of Medicine, Department of Pediatrics, 2023)
Background: Prompt management of respiratory distress (RD) among neonates is lifesaving. Electric cardiometry (EC) is not suitable for diagnosis, but its value in monitoring changes in cardiac parameters over time is in need of verification. Aim of the Work: To study EC hemodynamic parameters predictive ability of outcome in full- term newborns with RD. Materials and Methods: using electric cardiometry (EC) hemodynamic parameters were studied among 30 full term neonates with RD within the first 10 minutes of life and 2 hours later compared to another 30 without RD. The studied parameters were heart rate variability (HRV), cardiac output (CO), cardiac index (CI), stroke volume (SV), stroke index (SI), thoracic fluid content (TFC), stroke volume variation (SVV), index of contractility (ICON), left ventricular (LV) pre-ejection period (PEP), ejection time (ET), and systemic vascular resistance (SVR). Results: The mean ± SD gestational age of the studied group was 38.20 ± 1.19 weeks, weight was 3.03 ± 0.51 kilogram, females were 15 (50%), and males were 15 (50%) which was comparable to the control group (p=0.584), (p=0.284) and (p=0.436) respectively. The mean Apgar score was less among the RD group; at one minute it was 6 and at 5 minutes was 8 (p=0.0001) and (p=0.002). Initial HRV, CO, CI, SV, SI, TFC, SVV, ICON, LV, PEP, ET, and SVR were not different among both groups but there was a significant decrease in CI (p=0.033), HRV (p=0.030), SI (p = 0.017), and SV (p= 0.016) in the RD group after 2 hours. Those with RD, 20 (66.6%) improved and 10 (33.3%) were admitted to the neonatal intensive unit. Both groups with RD had comparable HRV, CI, CO, SV, SI, TFC, SVV, PEP, ICON, LVET, or SVR in initial and the 2 hour of life assessment (p= 0.860), (p= 0.071), (p= 0.932), (p= 0.260), (p= 0.548), (p= 0.338), (p= 0.744), (p= 0.488), (p= 0.392), (p= 0.983), (p= 0.066) respectively. Conclusion: Hemodynamic parameters assessed by electric cardiometry of full term neonates within 10 minutes of birth was not different among those with RD and those without. Electric cardiometry at 2 hours of life of those with RD was not predictive of outcome.